Associations between vigorous physical activity, social ties, social support, and self-reported health among older adults in Accra, Ghana. - Nestor Asiamah; Kyriakos Kouveliotis; Richard Eduafo; Richard Borkey (Public Library of Science (PLoS), 2023)
Meeting recommended vigorous physical activity (VPA) levels represents a hallmark for healthy living, but VPA in older populations is likely to lead to casualties that may compel older adults to underscore their health. This study examined the associations between VPA, social ties, social support, and self-reported health in an African sample of older adults. This study adopted the cross-sectional design. The study population was community-dwelling older adults aged 60 years or higher in Accra, Ghana. A total of 686 older adults responded to self-reported questionnaires. Data were analysed with the Pearson's chi-square test and binary logistic regression. The study found that older adults who had above 5 children were 3 times (AOR = 3.169; p = .002) more likely to participate in VPA for 30 minutes or more a day compared with their peers without children. Having social support from between 1 and 5 people was 28 times (AOR = 28.215; p = .000) more likely to result in good health compared to not having anyone to source social support from. Older adults who participated in VPA for 30 minutes or more were less likely (AOR = 0.129; p = 0.000) to report good health compared with those who participated in VPA for less than 30 minutes. We conclude that when social ties and other personal characteristics are adjusted for, prolonged VPA does not necessarily enhance self-reported health, and not all social ties contribute to VPA and self-reported health.